ANALISIS IMPLEMENTASI SISTEM PENGUPAHAN BERDASARKAN UNDANG-UNDANG NO. 13 TAHUN 2003 TENTANG KETENAGAKERJAAN DI PT.ENLKA MITRA PERKASA - Indah Suci Pirani; Rachmat Gustiana; Doddy Mulyono; Guntur Syahputra Saragih (Bussman Journal : Indonesian Journal of Business and Management, 2023)
The wage system is part of the protection of workers' rights which requires business institutions that have management and employ employees to pay wages. PT. Enlka Mitra Perkasa as a business institution that employs employees is included in the scope of business institutions that must provide wages in accordance with the provisions of Law Number 13 of 2003 concerning Manpower. Provisions in the Labor Law and its implementing regulations apply to employees of PT. Enlka Mighty Partners. In this study, the researcher proposed nyitepeeep nypynitiep ""How is the implementation of the wage system based on Law No. 13 of 2003 concerning Employment at PT. Enlka Mitra Perkasa? One of the research objectives is to find out about wages and their implementation at PT Enlka Mitra Perkasa. Type of research Field research was used in this study.The data collection tool used interviews, documentation, and observation.The data analysis technique used qualitative data analysis techniques which consisted of three stages, namely: data reduction, data display and conclusion/verification. The results of the study show that the minimum wage at PT Enlka Mitra Perkasa is not in accordance with the 2023 Tangerang City UMK of Rp. 4,584,519, per month. The wage system at PT. Enlka Mitra Perkasa pays attention to achievements, positions and length of service. For permanent employees, the lowest salary is Rp. 3.300.000,- Determination of employee status is assessed from their performance during the training period. As for the training period, employees receive a salary of Rp. 2.500.000,- excluding meal allowance Rp. 12,000, - and transportation Rp. 7,000,- PT. Enlka Mitra Perkasa provides bonuses, incentives and THR to employees. Bonuses are given to employees when they are able to sell products according to the target, the amount of incentives is given in accordance with the procedures and position of the employee